2009
DOI: 10.1590/s1415-47572009005000052
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genetic diversity in southern and southeastern Araucaria angustifolia (Bert.) O. Kuntze relict populations

Abstract: Habitat fragmentation and a decrease in population size may lead to a loss in population genetic diversity. For the first time, the reduction in genetic diversity in the northernmost limit of natural occurence (southeastern Brazil) of Araucaria angustifolia in comparison with populations in the main area of the species continuous natural distribution (southern Brazil), was tested. The 673 AFLPs markers revealed a high level of genetic diversity for the species (Ht = 0.27), despite anthropogenic influence throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
(62 reference statements)
2
9
0
1
Order By: Relevance
“…2b). This overall pattern of genetic structure is congruent with studies reported for natural populations evaluated with isozymes (Sousa et al 2004 nuclear SSR and AFLP markers (Stefenon et al 2007;Souza et al 2009). In addition, the structure estimated in this study using polymorphic nuclear SSR markers correlated broadly to genetic structure inferred for cpDNA haplotype (Stefenon et al 2019).…”
Section: Genetic Diversity and Differentiation Among Sampled Populationssupporting
confidence: 90%
See 2 more Smart Citations
“…2b). This overall pattern of genetic structure is congruent with studies reported for natural populations evaluated with isozymes (Sousa et al 2004 nuclear SSR and AFLP markers (Stefenon et al 2007;Souza et al 2009). In addition, the structure estimated in this study using polymorphic nuclear SSR markers correlated broadly to genetic structure inferred for cpDNA haplotype (Stefenon et al 2019).…”
Section: Genetic Diversity and Differentiation Among Sampled Populationssupporting
confidence: 90%
“…A total of 126 incidence records (progenies) were used to build the model, 91 of which corresponded to a southernmost geographical group and 35 to a northernmost geographical group. These groups were proposed based on previous evidence from independent research on araucaria (Sousa 2001;Sousa et al 2009 Precipitation of Warmest Quarter, and P19: Precipitation of Coldest Quarter) derived from temperature and moisture data (the "BioClim" layers), plus altitude. Thirty arc-second grids were obtained from WorldClim (http://www.world clim.org) and cropped to the study region.…”
Section: Environmental Niche Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…All species of T. (Nectarodiaeta) seem to be associated with forest environments, especially the so‐called mixed ombrophilous forests, characterized by the outstanding presence of Araucaria angustifolia Kuntze trees (Freitas & Silveira, ). This same distributional pattern was recognized for different plant species by Simpson () and for different bee lineages by Silveira & Cure () and Silveira (), and could be explained as resulting from the expansions and retractions of those forests during the Quaternary (Kershaw & Wagstaff, ; de Souza et al , ; Lauterjung et al , ). Within this subgenus, T. (Nectarodiaeta) oliveirae may be the single exception to this forest association, being known only from regions without forested environments.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, this role for parrots could be translated to the genetic population structure of Araucaria populations. Population genetic studies were carried out on the four species studied here (Bekessy et al, 2002;Pye and Gadek, 2004;Stefenon et al, 2007;Pye et al, 2009;Souza et al, 2009), and results were interpreted under the assumption that only pollen dispersal is responsible for long-range gene flow in these species. This assumption comes from a thorough paternity study conducted on seeds, seedlings and juveniles of A. angustifolia (Bittencourt and Sebbenn, 2007).…”
Section: Future Research Avenuesmentioning
confidence: 99%